La crisi di Suez del 1956 - Vedovato, Giuseppe (Rivista di studi politici internazionali, 2011)
Working on important documents, Professor Vedovato reconstructs an overall political and thorough diplomatic study of the 1956 Suez crisis, with a direct experience of matters because he was a protagonist of Italian parliamentary discussion about this problem. His balanced analysis was considered important by his political adversaries too. Vedovato’s approach considers the Suez crisis the turning point in Arabian world history and so in Arabian-Israeli conflict, in Euro-Atlantic relations and in Italian politics. Italian Foreign Minister Mr. Martino’s policy was based on national interests and on Atlantic loyalty and friendship with Arabian countries, being able to summarize political differences among the parties of the government’s majority and among Demochristian party too. While Italy played a role in stability search, on the contrary there were disagreements among Nato powers. The United Kingdom and France looked at gunboat diplomacy with an ancient colonial principle while the Usa thought of a new system of power in the Middle East, like Urss. The American government worked to prevent war, saving relationship with the heterogeneous Bandung Group. So all problems converged to the events happened on October 29, 1956. The correlation between Hungarian revolution and the timing of the Suez crisis produced a complex picture in the political context at the United Nations. Anyway, in this difficult context, Italy acquired a new international respect lost during World War II. L’Auteur reconstitue, à partir de documents importants, le cadre diplomatique et politique de la crise de Suez qui éclata en 1956. Il était parmi les protagonistes du débat parlementaire à la Chambre italienne et son analyse fut appréciée et respectée même par ses adversaires politiques. Vedovato montre que les événements qui survinrent à Suez sont le tournant de l’histoire du monde arabe, des relations israélo-arabes, des relations atlantiques, et de la politique étrangère italienne. Le ministre italien des Affaires étrangères, M. Martino, conduit sa politique selon les intérêts économiques nationaux, mais aussi en defendant, avec la fidélité atlantique, l’amitié des pays arabes. Par conséquent, il sut surmonter les différences politiques qui existaient entre les parties de l’alliance gouvernementale et dans le parti demochrétien même. Tandis que l’Italie jouait son rôle pour stabiliser la paix, l’Angleterre et la France, anciennes puissances maritimes et mondiales, voyaient encore les choses dans leur ancienne perspective. Le gouvernement américain travaillait pour empêcher la guerre et pour sauvegarder ses rélations avec le Groupe de Bandung qui, toutefois, n’était pas homogène. Enfin, toutes questions convergèrent dans la guerre, le 29 octobre 1956. Le parallélisme entre la révolution hongroise et l’intervention francoanglo- israélienne à Suez compliqua le débat à l’Onu. Dans cette affaire, l’Italie retrouva un rôle international qu’elle avait perdu avec sa défaite lors de la Seconde Guerre mondiale. PAROLE CHIAVE: Canale di Suez; Medio Oriente; Nasser; Politica estera italiana; Gaetano Martino.